2010
DOI: 10.1128/aac.00447-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Antituberculosis Drugs in Pulmonary Tuberculosis Patients with Type 2 Diabetes

Abstract: Altered pharmacokinetics of antituberculosis drugs may contribute to an increased risk of tuberculosis treatment failure for diabetic patients. We previously found that rifampin exposure was 2-fold lower in diabetic than in nondiabetic tuberculosis patients during the continuation phase of treatment. We now examined the influence of diabetes on the pharmacokinetics of antituberculosis drugs in the intensive phase of tuberculosis treatment, and we evaluated the effect of glycemic control. For this purpose, 18 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 23 publications
(33 reference statements)
7
97
3
Order By: Relevance
“…The mean age (48.7 y) of the male patients was greater when compared to a similar study conducted by Mendez (2012) [14]. The mean age of PTB patients with diabetes and without diabetes in the present study was in contrast to that conducted by Ruslami et al (2010) [15]. However, our results were similar to Ruslami et al when the statistical significance in body weight between these groups was analyzed [15].…”
Section: Fig 2: Distribution Based On Cat Regimencontrasting
confidence: 57%
See 2 more Smart Citations
“…The mean age (48.7 y) of the male patients was greater when compared to a similar study conducted by Mendez (2012) [14]. The mean age of PTB patients with diabetes and without diabetes in the present study was in contrast to that conducted by Ruslami et al (2010) [15]. However, our results were similar to Ruslami et al when the statistical significance in body weight between these groups was analyzed [15].…”
Section: Fig 2: Distribution Based On Cat Regimencontrasting
confidence: 57%
“…The mean age of PTB patients with diabetes and without diabetes in the present study was in contrast to that conducted by Ruslami et al (2010) [15]. However, our results were similar to Ruslami et al when the statistical significance in body weight between these groups was analyzed [15]. Exposure to rifampicin has been reported to be two-fold lower in diabetic than in non-diabetic patients with tuberculosis during the continuation phase of treatment [14].…”
Section: Fig 2: Distribution Based On Cat Regimencontrasting
confidence: 57%
See 1 more Smart Citation
“…The top concentration prepared for fosfomycin MPC determination was 64 mg ml À1 , which is double the resistant or susceptible breakpoint concentration of Staphylococcus to fosfomycin (32 mg ml À1 ) according to EUCAST. 17 The concentrations of levofloxacin (2 mg ml À1 ) and rifampicin (2 or 4 mg ml À1 ) used in combination with vancomycin reflect their mean serum concentrations at steady state in healthy adults 21 and adult pulmonary tuberculosis patients, 22,23 respectively. The concentration of fosfomycin (32 mg ml À1 ) used in combination with vancomycin equals the susceptible breakpoint concentration of staphylococci but is far below the mean serum concentrations at steady state according to currently recommended dosing regimens.…”
Section: Synergy Testingmentioning
confidence: 99%
“…This is considered to be related to the change in antituberculosis drug pharmacokinetics in diabetic patients. In a study by Ruslami and colleagues, it was observed that there was no difference between diabetic and non-diabetic patients in rifampicin, pyrazinamid and ethambutol pharmacokinetics in the intensive phase of treatment; but in the continued phase of treatment, pharmacokinetics of rifampicin were changed and its blood concentration was decreased (24)(25)(26). Although this can be explained by weight gain and other possible causes, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%